2023
DOI: 10.1002/edm2.407
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between haematological parameters and metabolic syndrome: A population‐based study

Abstract: Background: Metabolic syndrome (MetS) is a global public health concern. Chronic inflammation plays a role in MetS; haematological inflammatory parameters can be used as MetS predicting factors. Objective: Hereditary and environmental factors play an important role in the development of MetS. This study aimed to determine the relationship between haematological parameters and MetS in the adult population of southeastern Iran, Kerman. Methods: This cross-sectional study was a sub-analysis of 1033 subjects who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Regarding research design, all studies were observational and two were RCTs. Twenty-nine studies 7 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 defined MetS according to the third report of the National Cholesterol Education Program (NCEP-Adult Treatment Panel (ATP III) 40 . Twelve studies 4 41 42 43 44 45 46 47 48 49 50 51 assessed MetS using the International Diabetes Federation (IDF) criteria 52 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding research design, all studies were observational and two were RCTs. Twenty-nine studies 7 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 defined MetS according to the third report of the National Cholesterol Education Program (NCEP-Adult Treatment Panel (ATP III) 40 . Twelve studies 4 41 42 43 44 45 46 47 48 49 50 51 assessed MetS using the International Diabetes Federation (IDF) criteria 52 .…”
Section: Resultsmentioning
confidence: 99%
“…width (RDW) have been linked significantly to MetS, according to certain studies 7 . Additionally, insulin resistance and a pro-inflammatory, pro-thrombotic state in MetS lead to metabolic imbalances, including elevated platelet count 4 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 In addition, in a cross-sectional study of 1033 adults from southeastern Iran, NHR was found to be a valuable biomarker for assessing the risk of metabolic syndrome. 13 Taken together, NHR, a novel indicator of inflammatory cells and cholesterol, may comprehensively reflect the inflammatory state and dyslipidemia in diseases such as coronary heart disease, stroke, and metabolic syndrome. The relationship between NHR and NAFLD has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…13,30 Similarly, a cross-sectional study based on the population of Kerman in southeast Iran also confirmed a positive correlation between WBC and its subcomponent cells counts such as neutrophil, lymphocyte and monocyte and the severity of MetS, especially in females, but NLR was not recognized as a predictor for MetS. 31 Hence, the relationship and mechanism between NLR and MetS needed to be further studied.…”
mentioning
confidence: 94%